2022
DOI: 10.3390/ijms23169303
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tocochromanols in Tolerance of Cereals to Biotic Stresses: Specific Focus on Pathogenic and Toxigenic Fungal Species

Abstract: Fungal pathogens capable of producing mycotoxins are one of the main threats to the cultivation of cereals and the safety of the harvested kernels. Improving the resistance of crops to fungal disease and accumulation of mycotoxins is therefore a crucial issue. Achieving this goal requires a deep understanding of plant defense mechanisms, most of them involving specialized metabolites. However, while numerous studies have addressed the contribution of phenylpropanoids and carotenoids to plant chemical defense, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Biotic stresses are crucial constraints to the productivity of crop plants, especially under climate change conditions (Parihar et al, 2022), and lead to more than 20% crop yield losses (Savignac et al, 2022). Galewski et al identified specific genomic features associated with seedling rhizoctonia resistance by whole genome sequencing of selected and unselected bulk derived from a synthetic outcrossing sugar beet population and the genome-wide variation resulting from the selection.…”
Section: Biotic Stress-relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotic stresses are crucial constraints to the productivity of crop plants, especially under climate change conditions (Parihar et al, 2022), and lead to more than 20% crop yield losses (Savignac et al, 2022). Galewski et al identified specific genomic features associated with seedling rhizoctonia resistance by whole genome sequencing of selected and unselected bulk derived from a synthetic outcrossing sugar beet population and the genome-wide variation resulting from the selection.…”
Section: Biotic Stress-relatedmentioning
confidence: 99%
“…Biotic stresses are crucial constraints to the productivity of crop plants, especially under climate change conditions ( Parihar et al., 2022 ), and lead to more than 20% crop yield losses ( Savignac et al., 2022 ). Galewski et al.…”
Section: Biotic Stress-relatedmentioning
confidence: 99%
“…These problems are not only related to the severity of weather events during the growing season of cereal plants and may also affect the increased occurrence of plant pathogen infections during flowering 2 . In this context, protecting cereal plants from pathogenic fungi and insects (often vectors in the spread of fungal diseases) takes on particular importance 3 . The current global trend assumes reducing the use of chemical pesticides towards sustainable agriculture development and food security assurance.…”
Section: Introductionmentioning
confidence: 99%